Population Pharmacokinetic Analysis of Fevipiprant in Healthy Subjects and Asthma Patients using a Tukey’s g-and-h Distribution - Wang, Xinting; Bartels, Christian; Kulkarni, Swarupa; Sangana, Ramachandra; Jain, Monish; Zack, Julia; Yu, Jing (Drug research (Stuttgart), 2021)
Abstract Aim The objective of this analysis was to characterize the population pharmacokinetics (PK) of fevipiprant in asthma patients and to evaluate the effect of baseline covariates on the PK of fevipiprant. Methods PK data from 1281 healthy subjects or asthma patients were available after single or once daily dosing of fevipiprant. Population PK analysis was conducted to describe fevipiprant plasma concentration data using a non-linear mixed effect modeling approach. Results Fevipiprant PK was described by a two-compartment model with first-order absorption and first-order elimination. Exploration of fevipiprant PK in the population from the phase III studies revealed an over-dispersed and skewed distribution. This unusual distribution was described using Tukey’s g-and-h distribution (TGH) on the between-subject variability of apparent clearance (CL/F). The model identified a significant impact of disease status on CL/F, with the value in healthy subjects being 62% higher than that in asthma patients. Bodyweight, age and renal function showed statistically significant impact on fevipiprant clearance; however, compared with a typical asthma patient, the simulated difference in steady-state exposure was at most 16%. Conclusion Fevipiprant PK was described by a two-compartment model with first-order absorption and first-order elimination. The TGH distribution was appropriate to describe the over-dispersed and skewed PK data as observed in the current studies. Asthma patients had approximately 37% higher exposure than healthy subjects did. Other covariates changed exposure by at most 16%.